2014
DOI: 10.1007/s11869-014-0277-4
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, sources and exposure risks associated with particulate matter in the Middle East Area—a review

Abstract: Rapid economic expansion, industrialization, urbanisation and construction in the Middle East Area (MEA) have led to an increase in the levels of air pollution, resulting in serious effects on human health. For the first time, this article provides a comprehensive synthesis of the currently available published information which deals with atmospheric particulate matter (PM) in MEA. The focus of the article remains on the PM sources, monitoring, health impacts and source apportionment.The key objectives are to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 71 publications
4
55
0
1
Order By: Relevance
“…In prior studies conducted in the Middle East, dust was identified as the major source of PM 10 (Givehchi et al, 2013); however, contributions from anthropogenic sources to PM mass concentrations were found to be significant (> 82 % of total PM 10 mass, Al-Dabbous and Kumar, 2015; > 50 % of PM 10 , Tsiouri et al, 2015). Tsiouri et al (2015) summarized the major sources of PM 10 in ambient air in the Middle East as oil combustion, resuspended soil, road traffic, crustal dust, and marine aerosol; significant sources of PM 2.5 were oil combustion in power plants, resuspended soil, sand dust, and road traffic. Carbonaceous particles were estimated to account for 50-60 % of PM 2.5 in cities in the State of Palestine, Jordan, and Israel (Abdeen et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…In prior studies conducted in the Middle East, dust was identified as the major source of PM 10 (Givehchi et al, 2013); however, contributions from anthropogenic sources to PM mass concentrations were found to be significant (> 82 % of total PM 10 mass, Al-Dabbous and Kumar, 2015; > 50 % of PM 10 , Tsiouri et al, 2015). Tsiouri et al (2015) summarized the major sources of PM 10 in ambient air in the Middle East as oil combustion, resuspended soil, road traffic, crustal dust, and marine aerosol; significant sources of PM 2.5 were oil combustion in power plants, resuspended soil, sand dust, and road traffic. Carbonaceous particles were estimated to account for 50-60 % of PM 2.5 in cities in the State of Palestine, Jordan, and Israel (Abdeen et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…In arid and semi-arid regions a large part of PM 10 (particulate matter with aerodynamic diameter less than 10 lm) is comprised of crustal material from dust emissions (Tsiouri et al 2015). Dust aerosols can either originate locally or transported from thousands of kilometers away (Prospero et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…well as those resulted from industrial, agricultural, or natural sources (Kumar et al, 2013;Rasmussen et al, 2013). In the Middle East region, a major external source of indoor pollution is soil or dust particles that are loaded naturally or anthropogenically with hazardous chemicals and settle down in indoor environments (Al-Dabbous and Kumar, 2014;Tsiouri et al, 2014). Such soil particles constitute "house dust", which is defined as "a complex mixture of biologically derived material (such as animal dander and fungal spores), particulate matter (PM) deposited from the indoor aerosol, and soil particles brought in by the foot traffic (USEPA, 2011)".…”
Section: Introductionmentioning
confidence: 99%